Answer:
A. [tex]\frac{(x+1)^{2}}{4}+\frac{(y-2)^{2}}{9} =1[/tex]
Step-by-step explanation:
We have been given a graph and we are asked to write an equation for the ellipse shown in the graph.
Since we know that standard equation for ellipse is in form: [tex]\frac{(x-h)^{2}}{a^{2}}+\frac{(y-k)^{2}}{b^{2}} =1[/tex], where our ellipse is centered at (h,k), whose horizontal radius is a and vertical radius is b.
We can see from our diagram that center of our given ellipse is at point(-1,2)
We can see that our ellipse has a vertical radius of 5-2=3 units. The horizontal radius of our ellipse is [tex]1-(-1)=1+1=2[/tex] units long.
Now let us substitute our given values in standard ellipse equation to find the correct option.
[tex]\frac{(x-h)^{2}}{a^{2}}+\frac{(y-k)^{2}}{b^{2}} =1[/tex],
[tex]\frac{(x--1)^{2}}{2^{2}}+\frac{(y-2)^{2}}{3^{2}} =1[/tex]
[tex]\frac{(x+1)^{2}}{4}+\frac{(y-2)^{2}}{9} =1[/tex]
Upon looking at our given options we can see that option A is the correct choice.